Methodism in the Royal Navy, 1740-1815 - Pickering, Andrew Nelson (Wesley and Methodist studies, 2019)
The relationship between Methodism and the armed forces dates from the very early days of the movement. The Methodist soldier preachers of the eighteenth century have been the subject of considerable historical study; the navy has received much less attention. Owen Spencer Watkins recognized that evidence of Methodism in the Royal Navy was at most very occasional. The result is that a most interesting chapter in the history of our Church is lost to us.'1 There is a paucity of material, certainly in comparison with the army; however, it is possible to give sufficient evidence of a thriving Methodist subculture in the Royal Navy during the Revolutionary and Napoleonic Wars.